Arobust Hotelling-T2 test" - شاهين, حمزة اسماعيل (Journal of Economics and Administrative Sciences, 2014)
This research work as an attempt has been made to find robust estimations for Hotelling-T2 test when the data is from amultivariate normal distribution and the sample of the multivariate contain outliers also this research gives an easily high breakdown point robust consistent estimators of multivariate location and dispersion for multivariate analysis by using two types of robust estimators, of these methods are minimum covariance determinant estimator and reweighted minimum covariance determinant estimator.